High performance voltage output filter realizations using second generation voltage conveyor. Issue 9 (9th October 2018) - Safari, Leila; Barile, Gianluca; Ferri, Giuseppe; Stornelli, Vincenzo
Abstract: In this article, new voltage‐output filter realizations based on second generation voltage conveyor (VCII) as basic building block are presented. The results of this study show that VCII is a suitable candidate for applications requiring a voltage as filter output signal, considering that the availability of a low impedance voltage output terminal in VCII makes unnecessary the use of extra voltage buffers at the filter output, resulting in filter implementations with simpler structure, reduced power consumption, and chip area. New configurations of VCII based filters with first order low‐pass (LP), second order LP, and second order bandpass (BP) transfer functions are shown. The proposed circuits enjoy a very simple structure employing only one active element and four passive components. Simulation results for a VCII transistor implementation in a 0.35 μm standard CMOS technology and a supply voltage of ±1.65 V approve the presented theory.